Relationship of prolactin receptors to concanavalin A binding - Costlow, Mark E.; Gallagher, Patricia E. (Biochimica et biophysica acta, 1979)
Concanavalin A, which binds to specific carbohydrate determinants on the cell surface, was used to investigate the binding of prolactin to its receptors in liver membranes from female rats. The binding of 125I-labeled ovine prolactin to receptors was sharply inhibited by concanavalin A. This effect was reversed by the competitive sugar α-methyl-D-mannopyranoside and thus required the presence of specifically bound lectin. Concentrations of concanavalin A of up to 50 μg/ml caused a progressive decrease in the apparent affinity of the prolactin receptor for hormone. When higher concentrations were used, the number of available binding sites decreased. Concanavalin A-resistant receptors, about 30% of the total, had the same dissociation constant ( K d) as the controls. The binding of 125I-labeled concanavalin A in the same membrane preparations showed the presence of two distinct types of concanavalin A binding. At low concentrations, the lectin bound with high affinity ( K d ≈ 6.6 · 10 −8 M). At high lectin concentrations, low affinity ( K d ≈ 6.7 · 10 −5 M) binding predominated. Since high affinity concanavalin A binding was saturated at 50 μg/ml, this class of binding most likely alters the affinity of the prolactin receptor for hormone; low affinity concanavalin A binding may mask prolactin receptors, making them inaccessible to the hormone. Binding sites for concanavalin A and prolactin appear to be independent but closely related since (i) concanavalin A did not displace bound prolactin from its receptor, and (ii) detergent-solubilized 125I-labeled prolactin-receptor complexes bound to concanavalin A-Sepharose and were eluted by α-methyl- D-mannopyranoside.